READING IN THE ELEMENTARY SCHOOL SCIENCE PROGRAM. - Ediger, Marlow (Science Education, 1965)
The article discusses basic procedures in helping elementary children read content with meaning and understanding science. According to the author, prior to reading from an elementary school science textbook, pupils should have background experiences which will help them to understand what they are reading, and that pupils should be guided in observing pictures carefully in their science textbooks. As pupils read from their textbook, they will find new questions or problem areas which are of concern to them. He has also recommended the use motion picture film which shows the topic in science. His emphasis on the proposition that motivation to read and interest in reading should be present in pupils concludes the article.